(untitled) (Sains Humanika, 2021)
Islamic General Hospital X Boyolali applies Islamic-based HR management to his company. The purpose of this paper is to determine the implementation of Islamic values which had been applied by HR management in the process of employee selection and development. This research uses descriptive qualitative method with interviews, observations and documentations collecting data tools. Informants are people in HR department from lowest level to highest level management. As an Islamic hospital whose mission is to provide quality, shar’i and fair health services, the management of hospital always applies Islamic values in developing its human resource potential. Through the inculcation of Islamic values, it is expected that the quality of hospital human resources will improve in terms of devotion, professionalism of work, and welfare for all hospital stakeholders. The results of this study stated that Islamic values can improve discipline and productivity of employee performance. The Islamic aspect is shown by including the criteria for reading the Al-Qur’an and the compulsory reading prayer test in the selection and Al-Qur’an study and daily worship monitoring in employee development.